Immunization status of under-2 children in BRAC member and non-member households - Tarannum, Sabah; Hyder, S.M. Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
This study assessed the immunization status of children aged under 2 among BRAC member and non-member households. Data were obtained from a total of I ,872 children. during April 1994 to December 1996, residing in I 00 villages of 4 rural thana.,·. Namely Saturia, Santhia, Mirzapur and Kazipur Complete immunization coverage rate (children having all 6 vaccines) was lower among BRAC member households (77%) compared to non-member households (eligible and non-eligible) (80-82%). The immunizations coverage rates for BCG, OPT and polio were much higher (over 90%) in all gruops of households compared to the coverage for measles (around 60%). The difference between OPT and polio vaccines and memvership status was staristically significant (p<0.05). Immunization coverage was significantly (p<O.OO I) associated with different areas among different types of households, the coverage varing between 92% in saturia and 75% in Kazipur. It was also observed that the retention of card was not emphasized to the mothers and they were not the vaccine card; only 53% children had vaccine cards and the rest 47% did not It indicates that the campaign about vaccination was insufficient. To improve full immunization coverage all over the country, more campaign on immunization is needed. Also, BRAC should investigate why complete immunization was less among BRAC member households compared to non-member households.